Normas, competitividade e uso do território no município de Extrema - Minas Gerais, pós 1990. - Liska, Estevan Rodrigues (2018)
This research deals with a geographic situation of the municipality of Extrema in the south of Minas Gerais in the face of the phenomenon of territorial competitiveness. The municipality of Extrema has 34.344 inhabitants, according to estimates by the Brazilian Institute of Geography and Statistics (IBGE) for the year 2017, is in a favorable geographical position to investments and adopts an aggressive competitive policy, such as land operations and tax exemptions to companies, for the participation of investments. This federative entity has managed to attract several companies and significantly increased the tax collection over the years. Indicators such as the Municipal Human Development Index (0,732 in 2010 - IBGE) point to lower problems with regard to poverty, but that the municipal territory has been given over to hegemonic interests, imposing new logics of territorial use and organization to the population local. An understanding of the political field seems to us fundamental to the understanding of the attraction of economic agents to the place (particularly large industries). Municipal management based on the ideology of efficiency and entrepreneurship without treatment of public finances and motivation for economic growth by the rulers, throughout their mandates, created general conditions of production for the attraction of capital and foreigners, that become good social and economic conditions indicators. In this way, affirming that it is a modernization and development of products, specifically for an accumulation of capital, but that society is little benefited of the process. Finally, we conclude that, in Extrema, a territorial competitiveness is characterized by rivalry between the federated entities in the attraction of productive investments, which are involved in the installation of companies, generation of employment and income, using, in particular, the proliferation of norms that meet their demands.